Pediatric Hyphema with a Secondary Bleed: Case Report on Childhood Trauma. - Murray, Elizabeth (Optometry & Visual Performance, 2020)
Background: Ocular trauma in childhood can have a lasting effect and is usually preventable with proper education and eye protection. A common manifestation of ocular injury caused by compressive or blunt force trauma is hyphema, which is blood accumulation in the anterior chamber following a tear in the iris or angle structures. Case Report: A 6-year-old white male was referred by the local emergency department following a close-range airsoft gun shot to his left eye. He presented with extreme pain, photophobia, and blur. Visual acuities were attempted, but unsuccessful due to poor patient cooperation. Intraocular pressure was 12 OD and 9 OS. 3+ bulbar conjunctival injection, 2-3+ corneal edema greatest temporally, a small corneal abrasion, and a microhyphema were present. Seidel sign was negative. After 2 days of management, corneal abrasion had resolved, however, the hyphema had a secondary bleed filling 75% of the anterior chamber. A B-scan confirmed that the retina was flat and no vitreous hemorrhage was present. The patient was referred to pediatric ophthalmology and an anterior chamber washout was performed. Final visual acuity was 20/30. Conclusions: Childhood traumas related to sports and recreation are often preventable with proper eye protection. These ocular traumas pose a challenge for eye care providers, as children are often more difficult to examine and treat. As pediatric providers, we must educate patients, parents, and coaches on the importance of prevention.